2017
DOI: 10.1097/md.0000000000008677
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome affects narrow-band UVB phototherapy response in patients with psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease. Metabolic syndrome (MS) is a combination of central obesity, dyslipidemia, glucose intolerance, and elevated blood pressure. Many epidemiological surveys have revealed the association of psoriasis with MS. Narrowband ultraviolet radiation b (NB-UVB) is an effective and widely used treatment for psoriasis. The purpose of this study was to investigate whether the presence of MS in patient with psoriasis affects NB-UVB treatment and whether this syndrome correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Moreover, TNF inhibition is associated with weight gain, while drugs targeting the IL‐23/Th17 axis are not . In addition, high BMI has been associated with poor treatment response . Further, we found that IL‐22 and IL‐1RA correlated with BMI.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, TNF inhibition is associated with weight gain, while drugs targeting the IL‐23/Th17 axis are not . In addition, high BMI has been associated with poor treatment response . Further, we found that IL‐22 and IL‐1RA correlated with BMI.…”
Section: Discussionmentioning
confidence: 61%
“…Nearly all studies were done in populations with mean/median body mass index (BMI) >25 kg/m 2 (indicative of overweight/obesity), except for Rui et al, who differentiated outcomes by presence or absence of metabolic syndrome (MetS), such that those without MetS reported mean BMI <25 kg/m 2 . 19 Skin type was reported in 4 of the 10 studies, with some variability in Fitzpatrick skin type between reports (Table 2). In 5 of the 10 studies, findings were reported for data collected following the final treatment compared to that collected prior to treatment (at baseline).…”
Section: Methodology and Article Identificationmentioning
confidence: 99%
“…In three of four studies, blood concentrations of C-reactive protein (CRP), a marker of acute inflammation, were reduced following treatment with nbUVB, 23,27,28 with no difference reported in the fourth study, which was much shorter in therapy duration (2 weeks), 26 compared to the other three (of 8-12 weeks in length). Interleukin-6 (IL-6) was measured in four studies, with one reporting no effect 20 and others reporting reduced concentrations in blood 19,28,29 after nbUVB. Other less frequently measured markers of inflammation that were reduced in blood following nbUVB included ferritin, 23 interleukins IL-8, 20 IL-17, 19 IL-22, 20 and TNF 19 (although TNF was not reduced in Mehta et al 28 ).…”
Section: Effects Of Nbuvb On Other Measuresmentioning
confidence: 99%
See 2 more Smart Citations